Semi-quantitative MRI biomarkers of knee osteoarthritis progression in the FNIH biomarkers consortium cohort − Methodologic aspects and definition of change. Issue 1 (December 2016) - Roemer, Frank; Guermazi, Ali; Collins, Jamie; Losina, Elena; Nevitt, Michael; Lynch, John; Katz, Jeffrey; Kwoh, C.; Kraus, Virginia; Hunter, David
Abstract Background To describe the scoring methodology and MRI assessments used to evaluate the cross-sectional features observed in cases and controls, to define change over time for different MRI features, and to report the extent of changes over a 24-month period in the Foundation for National Institutes of Health Osteoarthritis Biomarkers Consortium study nested within the larger Osteoarthritis Initiative (OAI) Study. Methods We conducted a nested case–control study. Cases (n  = 406) were knees having both radiographic and pain progression. Controls (n  = 194) were knee osteoarthritis subjects who did not meet the case definition. Groups were matched for Kellgren-Lawrence grade and body mass index. MRIs were acquired using 3 T MRI systems and assessed using the semi-quantitative MOAKS system. MRIs were read at baseline and 24 months for cartilage damage, bone marrow lesions (BML), osteophytes, meniscal damage and extrusion, and Hoffa- and effusion-synovitis. We provide the definition and distribution of change in these biomarkers over time. Results Seventy-three percent of the cases had subregions with BML worsening (vs. 66 % in controls) (p  = 0.102). Little change in osteophytes was seen over 24 months. Twenty-eight percent of cases and 10 % of controls had worsening in meniscal scores in at least one subregion (p  < 0.001). Seventy-three percent of cases and 53 % of controls had at least one area with worsening in cartilage surface area (p  < 0.001). More cases experienced worsening in Hoffa- and effusion synovitis than controls (17 % vs. 6 % (p  < 0.001); 41 % vs. 18 % (p  < 0.001), respectively). Conclusions A wide range of MRI-detected structural pathologies was present in the FNIH cohort. More severe changes, especially for BMLs, cartilage and meniscal damage, were detected primarily among the case group suggesting that early changes in multiple structural domains are associated with radiographic worsening and symptomatic progression.